3, 5-Dimethoxy-4-hydroxy myricanol attenuated oxidative stress-induced toxicity on cardiomyoblast cells. (September 2021) - Wang, YL; Zhang, Y; Liu, T; Cui, J
Myocardial ischemia is the main reason for ischemic heart diseases. Antioxidant treatment is considered as a possible approach to prevent myocardial ischemia injury, because oxidative stress is a key factor triggering it. This study was to investigate the protective effects of 3, 5-dimethoxy-4-hydroxy myricanol (DHM) against oxidative stress-induced cytotoxicity on H9c2 cells and further explore its mechanisms. The oxidative stress and inflammatory response markers were detected by H2DCFDA fluorescent measurement, enzyme-linked immunosorbent assay (ELISA), real-time PCR and Western blot. Results showed DHM exerted inhibitory effects against H9c2 cell damage. Furthermore, DHM decreased oxidative stress in H9c2 cells through up-regulating protein expression of heme oxygenase-1 (HO-1) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2). Moreover, DHM inhibited inflammatory responses through down-regulating the protein expression of mitogen-activated protein kinases (MAPKs) and nuclear factor kappa B (NF-κB). DHM exerted protective activities against oxidative stress-induced cell damage, at least through decreasing oxidative stress and inhibiting inflammatory responses, indicating that DHM have the potential to be developed as therapeutic agents for the treatment of myocardial ischemia.